Recycling and upcycling in constraction - Gnatiuk, Liliia; Novik, Hanna; Melnyk, Maryna (Theory and practice of design, 2022)
Waste is a serious environmental problem that poses a threat to the environment. The article describes the features of the use of recycling and upcycling in the construction industry. Comparison of the possibilities of these two approaches is relevant for determining effective strategies for the use of recycled materials and products in the context of the post-war reconstruction of Ukraine. Article purpose is to manifest the possibilities of using materials used in construction and their scope in load-bearing structures and decorative elements. Modern methods of handling secondary materials in construction were evaluated by the method of analysis of literature sources. Based on the comparison of existing recycling and upcycling projects for the construction of new buildings, the possibilities of using construction and demolition waste and solid waste in construction are determined. In the construction industry, waste can be used in the following ways: through the reuse of materials generated during construction and demolition and recycling — processing waste into raw materials used in the production of building materials. There is also experience of successful use in construction of municipal solid waste generated not in the construction industry — upcycling. Materials and products for upcycling in construction are either the result of creative search of customers or executors of the project, or the result of previous organized work on the collection and sorting of solid waste. Therefore, in order to spread the effective use of upcycling, it is necessary to develop a solid waste management infrastructure and disseminate successful experience in project implementation. For efficient and cost-effective recycling on a large scale it is necessary to introduce and disseminate selective demolition practices; collection and separate storage of construction and demolition waste on the construction site; recycling and disposal of materials along with construction to reduce transportation costs